Impact of Organizational Structure and Culture on E-Government Implementation: A Survey of Local Government Employees in Yogyakarta Special Region, Indonesia - Ulung Pribadi (Innovar: Revista de Ciencias Administrativas y Sociales, 2023)
Developed and developing countries have implemented e-government to improve public services, being government organization a key factor influencing e-government effective deployment. Therefore, this study examined variables related to organizational structure and culture and their influence in predicting e- government implementation. This work involved the participation of 400 respondents from regencies and city employees and used a survey data-gathering approach and a purposive sample technique. A Likert scale was used to design the questions. The data were assessed by sem-pls for validity and reliability, as well as to test hypotheses and regression. In aspects of organizational structure, unit size and span of control, in contrast to unit grouping, have a positive and significant impact on e-government implementation. In addition, regarding organizational culture, cooperative attitude, obeying social norms, keeping harmony, and prioritizing duty, as opposed to strong ties to the community, empathy, and being honest and trustworthy, showed a positive and significant effect on e-government implementation. Moreover, independent variables had a substantial impact on dependent variables, as evidenced by an R-square of 0.865. This study has as its main limitations the research area, the number of respondents, and the length of the research period. Finally, theoretical and practical implications and suggestions for future studies are assessed.